2018
DOI: 10.1177/0894439318810387
|View full text |Cite
|
Sign up to set email alerts
|

Invitation Timing and Participation Rates in Online Panels: Findings From Two Survey Experiments

Abstract: Falling participation rates is one of the most significant challenges facing survey research today. To curb this negative trend, scholars have searched for factors that can increase and decrease citizens’ willingness to participate in surveys. In this article, we investigate the timing effects of survey invitation e-mails on participation rates in a university-based online panel with members of the Swedish public. Through two large-scale experimental studies, we examine whether the day of week ( N = 11,294) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 45 publications
(64 reference statements)
1
15
0
Order By: Relevance
“…Conversely, in a survey of 24,000 scientists and engineers, Sauermann and Roach (2013) found no significant effect of email day. However, emails sent on the weekend produced a significantly slower response (consistent with Lindgren et al 2020).…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…Conversely, in a survey of 24,000 scientists and engineers, Sauermann and Roach (2013) found no significant effect of email day. However, emails sent on the weekend produced a significantly slower response (consistent with Lindgren et al 2020).…”
Section: Introductionsupporting
confidence: 55%
“…Looking at individual surveys, Lewis and Hess (2017) found that Tuesday morning was the most effective time to send invitations and reminder emails for a survey of U.S. federal employees, while Faught et al (2004) found that Wednesday was best for emailing invitations to individuals sampled from U.S. manufacturing firms. Similarly, in a survey of Swedish panel members, Lindgren et al (2020) found that emailing on Wednesdays produced the highest participation rates after 24 hours and Saturdays and Sundays the lowest; however, after six days, there were no significant differences in participation rates by email send day. Conversely, in a survey of 24,000 scientists and engineers, Sauermann and Roach (2013) found no significant effect of email day.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the first five waves, we invited panellists on Fridays (letters were mailed on Thursdays). From wave six on, we changed the invitation day to Monday, as we expected higher response rates by inviting people at the beginning of a week based on findings from other studies (Lindgren et al 2020 ; Blom et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…We also randomly assign some participants to choose the timing of their email invitations, thereby allowing participants to pick the most convenient day. To our knowledge, only Lindgren and colleagues (2018) have allowed participants to choose timing of survey invitations or reminders. They found a positive effect of sending invitations and reminders at individually preferred times, but this effect diminished over time.…”
Section: Existing Literature On Survey Timing and Attritionmentioning
confidence: 99%